Inhibited action mechanisms of fire extinguishing powder compositions - Gorovykh Ольга Геннадьевна; Tumarovich Юрий Геннадьевич (Chrezvychaynye situatsii: obrazovanie i nauka, 2007)
The reactions flowing in flame with the formation of active particles and probable mechanisms of interaction of radicals with the surface of powder extinguishing compositions were considered, additional indexes for determining inhibited efficiency of minerals were supposed.